2020
DOI: 10.1136/bmjspcare-2020-002455
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care from the perspective of cancer physicians: a qualitative semistructured interviews study

Abstract: ObjectiveIntegrated palliative care for populations with cancer is now highly recommended. However, numerous physicians working in cancer care are still reluctant to refer patients to specialist palliative care teams. This study explores their perceptions of palliative care and factors influencing reasons to refer to specialist palliative care.MethodsWe used a qualitative methodology based on semistructured interviews with physicians working in cancer care, in two tertiary hospitals and one comprehensive cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Working with others was impacted by the FOF subscale Fear of Devaluing One's Self-Estimate, which is consistent to the literature suggesting that some professionals are reluctant to engage and work with palliative care teams in the care of their patients due to the fear that this indicates the failure of their treatment [24,52]. Given there were not more relationships shown with other FIF subscales might indicate that the 'working with others' questions on the SEPC scale do not accurately measure a person's likelihood to engage a palliative care team, but rather their con dence if they happen to work with other teams.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Working with others was impacted by the FOF subscale Fear of Devaluing One's Self-Estimate, which is consistent to the literature suggesting that some professionals are reluctant to engage and work with palliative care teams in the care of their patients due to the fear that this indicates the failure of their treatment [24,52]. Given there were not more relationships shown with other FIF subscales might indicate that the 'working with others' questions on the SEPC scale do not accurately measure a person's likelihood to engage a palliative care team, but rather their con dence if they happen to work with other teams.…”
Section: Discussionsupporting
confidence: 82%
“…Feelings of failure are elicited in clinicians when patients reject treatment, when negotiations fail, or when a patient's body no longer responds to treatment. Failure has been found to be shaped by social and cultural expectations of responsibility; coming both from clinician, peers in medical teams, and patients receiving support [16, 24,36,[50][51][52]. There may be a cyclical effect with FOF in healthcare settings; avoiding patient deaths and EOL discourse may further impede con dence and comfortableness within this area.…”
Section: Fear Of Failure: a Theoretical Contextmentioning
confidence: 99%
“…Named specialties of participants included physicians from intensive care, oncology, haematology, geriatric medicine, palliative medicine, general medicine, intensive care, surgery, renal medicine, respiratory medicine, cardiology and a pain specialist. One study31 captured data related to the training participants had had in palliative care and EOL communication. It reported that all physicians interviewed over the age of 40 years, which was 5 out of 18 participants, reported never having received training in palliative care.…”
Section: Resultsmentioning
confidence: 99%
“…Others pointed to the orientation of the researchers, indicating they were explorative,35 or involved psychologists at the interview stage 36. Three papers referred to using prompts to encourage participants to reflect on feelings,31 37 38 and one asked about the meanings they attributed to memorable experiences 39. Six papers were not clear about their method of drawing out emotional experiences from participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation